Cyclic cliticization in Icelandic - Sigurðsson, Einar Freyr; Wood, Jim (Nordic journal of linguistics, 2019)
This squib discusses the clitic DU (-du/-ðu/-tu) in Icelandic and compares it with other reduced forms of personal pronouns, such as ’ann (for hann ‘he’) and ’ún (for hún ‘she’). We show that there are various restrictions found on DU which are not found on other reduced forms of personal pronouns in Icelandic. We argue that whereas reduced forms such as ’ann and ’ún are morphophonologically conditioned, DU is syntactically conditioned; it is not only clause-bounded but also phase-bounded.